Management of hepatitis C in patients with chronic kidney disease - Carvalho-Filho, Roberto J (World J Gastroenterol, 2015)
Hepatitis C virus (HCV) infection is highly prevalent among chronic kidney disease (CKD) subjects under hemodialysis and in kidney transplantation (KT) recipients, being an important cause of morbidity and mortality in these patients. The vast majority of HCV chronic infections in the hemodialysis setting are currently attributable to nosocomial transmission. Acute and chronic hepatitis C exhibits distinct clinical and laboratorial features, which can impact on management and treatment decisions. In hemodialysis subjects, acute infections are usually asymptomatic and anicteric; since spontaneous viral clearance is very uncommon in this context, acute infections should be treated as soon as possible. In KT recipients, the occurrence of acute hepatitis C can have a more severe course, with a rapid progression of liver fibrosis. In these patients, it is recommended to use pegylated interferon (PEG-IFN) in combination with ribavirin, with doses adjusted according to estimated glomerular filtration rate. There is no evidence suggesting that chronic hepatitis C exhibits a more aggressive course in CKD subjects under conservative management. In these subjects, indication of treatment with PEG-IFN plus ribavirin relies on the CKD stage, rate of progression of renal dysfunction and the possibility of a preemptive transplant. HCV infection has been associated with both liver disease-related deaths and cardiovascular mortality in hemodialysis patients. Among those individuals, low HCV viral loads and the phenomenon of intermittent HCV viremia are often observed, and sequential HCV RNA monitoring is needed. Despite the poor tolerability and suboptimal efficacy of antiviral therapy in CKD patients, many patients can achieve sustained virological response, which improve patient and graft outcomes. Hepatitis C eradication before KT theoretically improves survival and reduces the occurrence of chronic graft nephropathy, de novo glomerulonephritis and post-transplant diabetes mellitus.